Examining Code-Switching Practices in Hilman Hariwijaya’s Makhluk Manis dalam Bis and Bunga untuk Poppi - Tia Martiana (Passage, 2013)
This study investigates types and functions of code-switching in two novels. Theanalysis is framed within Poplack‟s types of code-switching theory (1980) and Koziol‟s functions of code-switching theory (2000 as cited in Fauzia, 2008 and Hendriyani, 2012). The documents (novels) were analyzed through several stages, i.e. identifying the code-switching in the characters‟ conversations; classifying the code-switching into their types and functions; quantifying the frequency of each type and function; and interpreting and discussing the data obtained. The results of data analysis show that there are three types and 13 functions of code-switching in the characters‟ conversations in the two novels. Keywords: Lupus, Code-switching, Types and Functions of Code-switching.